Illustrated Book Design as Waste Education for Children Aged 7-9 Years in Semarang City - Sayid Mataram; Zahra Luthfi Karunia Afanin (TAMA: Journal of Visual Arts, 2023)
Garbage problems are common in Indonesia. The amount of waste disposed of in landfills is increasing every year. The waste problem is caused by a lack of public awareness regarding waste management. Therefore, it is necessary to educate the public to increase awareness of the environment. Education about environmental care given early on can prevent bad things that might happen in the future. The problem in this research is how to educate children to increase awareness of the environment using the educational media of illustrated books. This descriptive qualitative research refers to the ADDIE research model to create illustrated book media as an educational solution to waste problems. With educational media illustrated books that have been designed, children can understand the types of waste and get an education about waste. Waste that is disposed of is properly and correctly segregated for each type. Illustrated books have proven effective as educational media for children aged 7-9 years as evidenced by the ease with which children understand the types and sorting of waste Keywords: Education, Waste Management, Children, Illustrated Books